2022
DOI: 10.3389/fimmu.2022.825428
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibition of GSDMD by PEITC Reduces Hepatocyte Pyroptosis and Alleviates Acute Liver Injury in Mice

Abstract: Acute liver injury (ALI), often caused by viruses, alcohol, drugs, etc., is one of the most common clinical liver diseases. Although pyroptosis plays an important role in ALI, there is still a lack of effective clinical drugs related to this mechanism. Here, we show that phenethyl isothiocyanate (PEITC), a natural compound present in cruciferous vegetables, can significantly alleviate concanavalin A (ConA)-induced inflammatory liver damage and carbon tetrachloride (CCl4)-induced chemical liver damage in a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Other studies investigated the effect of inhibiting hepatocyte pyroptosis in severe forms of liver injury. Wang et al 20 show that phenethyl isothiocyanate (PEITC), a natural product found in cruciferous vegetables, can significantly reduce both chemical and inflammatory liver injury. Similar to JZLGD, PEITC targets NLRP3 and Caspase-1.…”
Section: Overview Of Pyroptosis and Gasdermin-dmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies investigated the effect of inhibiting hepatocyte pyroptosis in severe forms of liver injury. Wang et al 20 show that phenethyl isothiocyanate (PEITC), a natural product found in cruciferous vegetables, can significantly reduce both chemical and inflammatory liver injury. Similar to JZLGD, PEITC targets NLRP3 and Caspase-1.…”
Section: Overview Of Pyroptosis and Gasdermin-dmentioning
confidence: 99%
“…Additionally, PEITC directly inhibits GSDMD cleavage and membrane pore formation by binding to cysteine 191 on GSDMD. 20 …”
Section: Overview Of Pyroptosis and Gasdermin-dmentioning
confidence: 99%
“…Phenethyl isothiocyanate (PEITC) is a widely distributed natural compound derived from the secondary metabolites of Brassicaceae plants; it has antimicrobial, anti-inflammatory, and antioxidant properties [ 170 , 171 ]. Wang et al, by constructing a Con A-induced acute immune liver injury model in mice, found that PEITC could reduce NLRP3 production and casp1 and GSDMD cleavage in the liver of ALI-suffering mice and directly interact with the cysteine at position 191 of GSDMD to inhibit hepatocyte pyroptosis, thereby exerting a significant hepatoprotective effect [ 172 ]. The work of Shi et al showed that dimethyl fumarate promoted NLRP3 phosphorylation on Ser/Thr residues at specific sites of protein kinase A (PKA) and enhanced PKA signaling to inhibit NLRP3 inflammasome activation, pyroptosis, and IL-1 β Secretion, thereby treating Con A-induced AIH [ 173 ].…”
Section: Nlrp3 Inflammasome and Programmed Cell Death In Alimentioning
confidence: 99%
“…It has been revealed that the N-terminal domain of GSDMD is responsible for some of the negative consequences observed in metabolic liver illnesses, such as NAFLD. Some studies have found that inhibition of GSDMD protects mice from this type of liver disease ( 96 ). In contrast, GSDMD deficiency was found to cause more portal vein and lobular inflammation, a wider hepatic conjunctival necrotic area, higher serum transaminase levels, and more extensive hepatocyte apoptosis after ConA induction ( 86 ).…”
Section: Inflammasomes and Pyroptosis In Aildsmentioning
confidence: 99%